Tuberculosis menace: a case report of disseminated tuberculosis presenting as tubercular meningitis and long-segment cervical tuberculous myelitis in a 32-year-old man from rural India - Saket Satyasham Toshniwal; Jiwan S. Kinkar; Amit Toshniwal; Anshul Sood; Sunil Kumar; Sourya Acharya (Frontiers in Medicine)
This case report discusses an uncommon presentation of miliary tuberculosis as tubercular meningitis (TBM) and long-segment cervical tuberculous myelitis in a 32-year-old man from rural India. The patient presented with symptoms of fever, headache, neck stiffness, and gradual weakness in all four limbs. Hydrocephalic changes secondary to meningitis and involvement of the spinal cord were observed on neuroimaging and were correlated with clinical findings of cervical myelitis, confirming the diagnosis of TBM with cervical myelitis. TBM, together with cervical myelitis in patients with miliary tuberculosis (TB), is a rare manifestation in tubercular endemic countries, such as India. It is crucial to confirm the diagnosis and initiate antitubercular therapy (ATT) promptly in order to prevent neurological complications. In this context, the present case highlights the importance of considering TB in patients with neurological manifestations that are not characteristic of the most common diseases. This report also emphasizes the need to raise awareness and improve the management of tuberculosis in rural areas where there are few opportunities to access tertiary centers.